UPAYA PELESTARIAN BAHASA DAN BUDAYA MINAHASA MELALUI DIGITALISASI DAN PENERJEMAHAN NASKAH - Dewi Christa Kobis (Yayasan Literasi Sains Indonesia, 2023)
This research discusses the preservation of Minahasa language and culture through the actualization of manuscript translation and its digitization stages. This research specifically looks at seven Minahasa languages, namely Bantik, Ratahan, Tondano, Tonsea, Tontemboan, Tonsawang, and Tombulu. Seven languages are rarely used by local communities and are threatened with extinction. This will cause Minahasa culture to erode because language is one of the means to maintain the culture of a region let alone a nation. This research aims to look at the preservation efforts that have been made by various parties in the period of four decades. After conducting qualitative research in the form of a literature study, the author found that starting from the local government, academics, educational institutions, cultural activists and the Ministry of Education and Culture have made certain efforts such as translation actualized by making dictionaries or translations of other regional language books and digitizing manuscripts. This is very helpful for the preservation of Minahasa language and culture. However, more socialization is needed for young people to be able to love, care for, and be proud to use Minahasa Regional Language in daily conversations in order to preserve Minahasa culture.